A matched case-control study on the interaction of anxiety, depression, and circadian CLOCK genes (CLOCK, PER2, RORA) in sleep disorders among mental workers - Yi, Xiaoting; Ma, Xiaofan; Shi, Lingyun; Li, Xue (Frontiers in Public Health, 2025)
ObjectiveThe current status of the occurrence of anxiety, depression, and sleep disorders in mental workers was investigated. The effects of anxiety, depression, and CLOCK, PER2, and RORA gene polymorphisms and their interactions on sleep disorders were further analyzed, to provide scientific references for the reduction of the risk of the occurrence of sleep disorders in mental workers.MethodsAnxiety, depression, and sleep disorders in the study population were measured by applying the Self-Assessment Scale for Anxiety (SAS), the Self-Assessment Scale for Depression (SDS), and the Pittsburgh Sleep Quality Index (PSQI). The CLOCK, PER2, and RORA genes of 748 mental workers (374 of whom were randomly selected from the sleep disorder group and 374 of whom were randomly selected from the normal sleep group) were genotyped by imLDR™ genotyping technology, and the relationship between CLOCK, PER2, and RORA gene polymorphisms and their interactions with sleep disorders were analyzed.ResultsThe detection rate of sleep disorders among mental workers was 27.88%. There were significant differences in the rates of sleep disorders among mental workers of different genders, ages, marital status, shifts, education, title, occupation, and monthly income (p < 0.05). There was a difference in the prevalence of sleep disorders between groups with different levels of anxiety and depression (p < 0.001). Anxiety and depression scores were positively related to PSQI scores (rs = 0.626, rs = 0.661, p < 0.001) and their scores in all dimensions. The rs10462028 and rs11932595 of the CLOCK gene, the rs934945 of the PER2 gene, and the distribution of genotypes and allele frequencies of each genotype, as well as allele frequency, were significantly different in the sleep-disordered group and the normal-sleep group (both p < 0.001). The difference in distribution was also significant (all p < 0.05). The interaction of rs934945, anxiety, and depression (OR = 10.461, 95% CI: 3.695–29.621) increased the risk of sleep disorders in mental workers (p < 0.05).ConclusionMental workers experience significant sleep disorders, so effective measures should be taken to reduce anxiety and depression. The interaction of rs934945, anxiety, and depression was associated with a higher prevalence of sleep disorders in mental workers.